Effect of particle concentration on the microstructural and macromechanical properties of biocompatible magnetic hydrogels. Issue 16 (30th March 2017) - Bonhome-Espinosa, A. B.; Campos, F.; Rodriguez, I. A.; Carriel, V.; Marins, J. A.; Zubarev, A.; Duran, J. D. G.; Lopez-Lopez, M. T.
Abstract : Embedding magnetic nanoparticles in fibrin hydrogels dramatically alters the microstructure of the hydrogels and strongly enhances their mechanical properties. Abstract : We analyze the effect of nanoparticle concentration on the physical properties of magnetic hydrogels consisting of polymer networks of the human fibrin biopolymer with embedded magnetic particles, swollen by a water-based solution. We prepared these magnetic hydrogels by polymerization of mixtures consisting mainly of human plasma and magnetic nanoparticles with OH − functionalization. Microscopic observations revealed that magnetic hydrogels presented some cluster-like knots that were connected by several fibrin threads. By contrast, nonmagnetic hydrogels presented a homogeneous net-like structure with only individual connections between pairs of fibers. The rheological analysis demonstrated that the rigidity modulus, as well as the viscoelastic moduli, increased quadratically with nanoparticle content following a square-like function. Furthermore, we found that time for gel point was shorter in the presence of magnetic nanoparticles. Thus, we can conclude that nanoparticles favor the cross-linking process, serving as nucleation sites for the attachment of the fibrin polymer. Attraction between the positive groups of the fibrinogen, from which the fibrin is polymerized, and the negative OH − groups of the magnetic particle surface qualitatively justifies the positive role of the nanoparticles in the enhancement of the mechanical properties of the magnetic hydrogels. Indeed, we developed a theoretical model that semiquantitatively explains the experimental results by assuming the indirect attraction of the fibrinogen through the attached nanoparticles. Due to this attraction the monomers condense into nuclei of the dense phase and by the end of the polymerization process the nuclei (knots) of the dense phase cross-link the fibrin threads, which enhances their mechanical properties.